1) Factoriser A=4x²-12x+9 puis B=4x²-12x+9+(2x-3)(3x-1)

2Reprendre la question prècèdente avec :

a) C= x²+2x+1 et D=x²+2x+1-8x(x+1)

b) E= 16+8x+x² et F=(x+16)(x+4)-(x²+8x+16)

c) G=25x² -9 et H=(5x+3) (5x+9)-(25x²-9)

1

Réponses

2012-12-18T15:17:58+01:00

4x²-12x+9

2x(2x-6)+9

 

 

4x²-12x+9+(2x-3)(3x-1)

2x(2x-6)+9+6x²-2x-9x+3

2x(2x-6)+9+6x²-11x+3

2x(2x-6)+12+6x²-11x

 

 

c= x(x+2)+1

x²2+2x+1-8x²-8

7x²+2x-7

 

 

e= 4(2x²-4x)

f=x²+4x+16x+64-x(x+8)+16

 

x²+20x+64-x(x+8)+16

x(x-20)+64-x(x+8)+16

x(x-12)+80